Molecular characterization and haplotypes of hydatid cyst isolates collected from humans and ruminants in Setif Province (northeast of Algeria) based on mitochondrial cytochrome C oxidase subunit 1 (mt-CO1) gene sequences - Kheninef, Amina; Celik, Figen; Aissaoui, Lynda; Simsek, Sami (Springer, 2024)
Cystic echinococcosis (CE) is a disease that can be transmitted from animals to humans, caused by the metacestode of Echinococcus granulosus. The disease has significant health and economic impacts worldwide, particularly in endemic areas. The study aimed to evaluate the prevalence of hydatid cysts in ruminants (cattle and sheep) (n = 2060) from the Setif Province of Algeria using microscopy. The results showed that hydatid cysts were detected in 9.6% (198/2060) of ruminants, with a higher prevalence in cattle (16.8%; 56/333) compared to sheep (8.2%; 142/1727). Molecular techniques were used to analyze a subset of animals consisting of 30 sheep and 4 cattle. Specifically, a fragment of the mitochondrial cytochrome c oxidase subunit 1 (mt-CO1) gene was sequenced and compared to sequences from seven humans from the same region. The results indicated that all isolates were identified as E. granulosus sensu stricto. Haplotype analysis identified 19 E. granulosuss.s. haplotypes arranged like a star, with the dominant haplotype (Hap04) at the center. Hap04 has been assigned a total of 17 positives, including positives from sheep, cattle, and two humans. This study is noteworthy for being the first to use a molecular approach to human and ruminant echinococcosis in Setif, a significant breeding region in Algeria.
Keywords: Echinococcus granulosus sensu stricto; Mt-CO1; Hydatid cyst; Ruminant; Human; Haplotype; Algeria